Response 0f Two Varieties of Cryptocoryne ciliata (Roxburgh) Schott to Shading and Water Depth - Nancy, Anak Majing. (Universiti Malaysia Sarawak (UNIMAS), 2007)
The .;;tudy on response of shading and waler depth o n the g rowth patte rn and biomass allocauo n of twQ van~t ;:; l",\ f Cn plocOlyn e cillala (Rox burgh) SchOl1 (A ra eea) was cond ucted in greenhouse co ndition at Uni verqti Malaysia Sarawak (UNIMAS). Plants matena ls and med ia were co li eCled from Kamp ung Terasi. KOla $ ama rahan, Sarawak. Samples were cu lti va ted a t diffe rent shade levels (25% shad ing, 50% shading and 75% shadi ng) and d ifferent \\Llter depOl regimes (0 em, 15 cm and 30 em). T he tota l dry wl!ight of C. ellUl/a var. ciliata was hi ghe<;l al 5tltl o shadin g and IS em water depth WiUl 0.3 743g and OA874 g each esp e~ti ve y and the lowest lo ta l dry weIght of C. crlialO var. ciliata was at 75% shadlllg and 30 em wa ter depth wi th (l ,2289g and 0 .3 158g each respective ly. Total dry \\ t: lght of C. ciliata va l". latl(o lia was rughest at 50% shad ing and 0 em wale r depth with O.5232g and O.S IIlRg I:aeh respecti ve ly. The owe~ t tota l dry wejght of C cdiata val'. latlfollO was at 75~/ll shadtng (O.3095g) and 30 em water depth (OA 009g). As for gro\.Vth aly~i~ , the total number o f leaves C cdiata va l' ciliala .:;howed significantly lower at 2S'> (1 shadmg and 30 em waler depth . However, C ciliaw var lal(folia recorded no ~i nifl ca nl dd"le renee for a ll shading and water depth rt:g i.mes.